The Role of Domestic Investment: A Case Study in Surakarta Karesidenan, Indonesia - Muchsin Muchsin; Rahmat Saleh (Jurnal Simki Economic, 2025)
The research aims to identify the factors that influence Domestic Investment (PMDN) in the Surakarta Karesidenan region. The research considers several aspects of variables as influencing factors, namely Road Length, Water Distribution, Labor, and Gross Regional Domestic Product. The data collection method is in the form of secondary data sources from the Central Bureau of Statistics, DPMPTSP Central Java. Observation of panel data time dimension research data in 2013-2018, covering the area used, including 7 (seven) districts/cities included in the Surakarta ex-Karesidenan, the number of observation data samples amounted to 42 samples. This study did not include the 2019-2024 period in the analysis because the global economic crisis due to the COVID-19 pandemic caused the PMDN economy to shift its priorities. In this case, companies will focus more on crisis management and divert already scarce financial resources to address the health and economic consequences of the COVID-19 pandemic, so companies will likely delay many of their investments and policies. The estimation method used is using panel data in individual effect (fixed effect) models. The results showed that partial analysis showed that road infrastructure does not affect domestic investment. Water infrastructure does not affect Domestic Investment. However, the research findings show that labor has a significant negative effect on domestic investment, and gross regional domestic product has a significant positive effect on domestic investment in the Surakarta Karesidenan region.